Acts of John - McCollum, Joey; Niedergall, Brent; Demars, Derek G. T.; Howell, Bobby; Young, Stephen M. (Brepols library of Christian sources, 2022)
The 'Acts of John' is a second- or third-century work of unknown authorship combining elements of the apocryphal acts and pious romance genres. It was labeled heretical by both Eusebius and Augustine, and condemned at the Second Council of Nicea (787). Scholars debate the influence of Gnosticism and docetism upon the work.00This narrative presents the lifelong ministry of the apostle John preaching and performing miracles in Ephesus, Smyrna, and elsewhere. At different turns in the exciting account, John resurrects the dead, reunites families, heals the sick, confronts pagan opponents, commands bedbugs, and divulges mysteries about his travels with Jesus.00The present edition offers the celebrated Greek text of Junod and Kaestli ('Corpus Christianorum, Series Apocryphorum', 1-2, 1983) alongside a new English translation on the facing pages, complete with hundreds of cross-references and other helpful notes for the reader